# make x the subject

Watch
Announcements

Page 1 of 1

Go to first unread

Skip to page:

This discussion is closed.

Report

#3

(Original post by

y=x-5 rearrange the formulae to make x the subject

**Harryacko**)y=x-5 rearrange the formulae to make x the subject

Well it's x=y+5

5

Report

#5

(Original post by

y=x-5 rearrange the formulae to make x the subject

**Harryacko**)y=x-5 rearrange the formulae to make x the subject

To make x the subject, you need to 'move' the -5 from the right hand side of the equation onto the left hand side.

We do this by adding 5 to both sides. This is because -5 + 5 = 0 and so we will simply be left with: y + 5 = x + 0 which is the same as y+5 = x. This is the right answer, but we usually prefer to write it as x = y+5.

Now try making x the subject of the following:

(1) y = x + 2

(2) y = 2 - x

(3) 2y + 3 = 2x -1

2

Report

#8

(Original post by

X/a(squared) 3b = 2c Make x the subject

**Hello hshsb**)X/a(squared) 3b = 2c Make x the subject

sorry I can't quite explain what I did as I just did it in my head but it's about dividing anything on the left of the = to get X on it's own

0

Report

#9

X/3bA^2 = 2c... The question, just rearranged so it's simpler to think out.

Now we have to make X, the subject

If something is divided by another thing and you wish to make the whatever is on the top the subject, in this case X. You simply multiply the bottom to each side of the question.

X =(A^2) (3B) (2C)

=6A^2BC

Now we have to make X, the subject

If something is divided by another thing and you wish to make the whatever is on the top the subject, in this case X. You simply multiply the bottom to each side of the question.

X =(A^2) (3B) (2C)

=6A^2BC

0

Report

#13

xy-x=a

Factorise

x(y-1)=a

Bring y-1 to the other side through division

x=a/y-1

Last edited by Filipina.x; 1 year ago

0

Report

#14

(Original post by

Take your x’s to one side

xy-x=a

Factorise

x(y-1)=a

Bring y-1 to the other side through division

x=a/y-1

**Filipina.x**)Take your x’s to one side

xy-x=a

Factorise

x(y-1)=a

Bring y-1 to the other side through division

x=a/y-1

0

Report

#15

How can your brother be your cousin?!?!?! Are you a troll?!?!?!?! I need answers?!?!?!?

0

Report

#16

(Original post by

y=x-5 rearrange the formulae to make x the subject

**Harryacko**)y=x-5 rearrange the formulae to make x the subject

x=y+5

0

Report

#19

y=x-5 rearrange the formulae to make x the subject

That's how you do it.

-multiply both sides by 2

-now take square roots of both sides

-rewrite everything in terms of powers

Now the problem is you've got powers to deal with so best thing here is to take logs of both sides.

SO,

now you can use the logarithmic power rule logb(x y) = y ∙ logb(x)

So this becomes:

let's rearrange and factorize:

now you have to find a way to remove logs from both sides otherwise we can not change subject right? so because we need same base which is log, so they cancel out !

you have to rewrite -1 as logs so we have logs on both sides. i didn't write before but all logs here were base 10

so -1 in log 10 base is log (10) (10^-1)

so this becomes

Use logarithmic power rule again to bring -1 as power

now logs cancel out and you're left with

You can not make x subject till x is not alone in one side so lets first rearrange:

and now divide both sides by 2.

It's actually quite simple but you need to remember logs and their properties.

That's how you do it.

-multiply both sides by 2

**2y=2x-10**-now take square roots of both sides

**Sqrt(2y) = sqrt(2x) - sqrt(10)**-rewrite everything in terms of powers

**2y^(1/2) = 2x^(1/2) - 10^(1/2)**Now the problem is you've got powers to deal with so best thing here is to take logs of both sides.

SO,

**log 2y^(1/2) = log 2x^(1/2) - log 10^(1/2)**now you can use the logarithmic power rule logb(x y) = y ∙ logb(x)

So this becomes:

**1/2 * log 2y = 1/2 * log 2x -1/2 * log 10**let's rearrange and factorize:

**1/2 * log 2y - 1/2 * log 2x = -1/2 log 10****1/2 (log 2y - log 2x)= -1/2 log 10**Divide both sides by 1/2**log(2y -2x) = -1**now you have to find a way to remove logs from both sides otherwise we can not change subject right? so because we need same base which is log, so they cancel out !

you have to rewrite -1 as logs so we have logs on both sides. i didn't write before but all logs here were base 10

so -1 in log 10 base is log (10) (10^-1)

so this becomes

**Log(10)(2y-2x) = -1 log (10)**Use logarithmic power rule again to bring -1 as power

**Log (10)(2y-2x)= log(10)^1**now logs cancel out and you're left with

**2y -2x = 10**You can not make x subject till x is not alone in one side so lets first rearrange:

**2x = 2y -10**and now divide both sides by 2.

**x = 5 - y**It's actually quite simple but you need to remember logs and their properties.

1

X

Page 1 of 1

Go to first unread

Skip to page:

new posts

Back

to top

to top